Incidencia de los trastornos del estado de animo en los pacientes con Diabetes del Instituto Ecuatoriano de Seguridad Social en el año 2011. - Reyes Pacheco, Cinthya Johanna (2014)
In this research it was addressed on the incidence of mood disorder in patients with diabetes Ecuadorian Social Security Institute in the city of Machala 2011.